MO223: Contribution of Interstitial CD138 + Plasma Cells on the Renal Outcome in Patients with Anca-Associated Vasculitis. (3rd May 2022) - Odler, Balazs; Haefner, Johannes M; Pollheimer, Marion J; Schabhuettl, Corinna; Krall, Marcell; Rosenkranz, Alexander; Eller, Kathrin
Abstract: BACKGROUND AND AIMS: Plasma cells (PC) are the most differentiated antibody and cytokine-producing B lineage cells and are thought to contribute to the perpetuation of inflammation in patients with ANCA-associated vasculitis (AAV). Agents targeting PCs are of interest in AAV, however, little is known about the role of interstitial CD138 + PCs in these patients. In this study, we aim to demonstrate the impact of this cell population in the prediction of renal outcomes in patients with AAV. METHOD: Forty AAV patients with glomerulonephritis, diagnosed between 2014 and 2018 at the Division of Nephrology of the Medical University of Graz were included and followed for 36 months. Histological assessments using the kidney allograft Banff classification were performed to describe the tubulointerstitial (TI) damages. Immunohistochemistry analysis was performed in 29 patients to assess the renal interstitial CD138 + cell expression. More than ten CD138 + cells per high power field were stated as high expression (excluding CD138 staining of renal tubular epithelial cells). Changes in kidney function, the incidence of renal relapses (RR), and end-stage renal disease (ESRD) were analyzed. RESULTS: In the kidney biopsies, N = 21 (72%) patients had a high expression of CD138 + plasma cells. No significant difference was observed in PR3 and MPO serotypes in the group of patients with high CD138 + cell expression (43% versus 57%, P = .793). In addition, no significant difference was seen in the changes in kidney function and the incidence of RR or ESRD between the groups with high and low expression of CD138 + cells during the follow-up period. However, patients with more severe TI damage had more severe proteinuria urinary albumin/creatinine ratio: 51 [interquartile range (IQR) 42–123] versus 360 (IQR 202–1112) mg/g Creatinine; P = .016 at 3-year follow-up, and tended to have a higher rate of RR and ESRD [i0/i1: N = 2/18 (11%) versus i2/i3: N = 6/22 (27%), P = .258 and i0/i1: N = 2/18 (11%) versus i2/i3: N = 6/22 (27%), P = .258, respectively]. CONCLUSION: Our data indicate a significant proportion of CD138 + PCs in kidney specimens of patients with AAV. Despite the lack of association between this cell population and our cohort's renal outcome, these results provide additional insights on the renal B-cell clusters in patients with AAV. In addition, our findings go along with already existing data on the association between extended TI damage and worse renal outcome.